Improving Elementary After-school Program for Child Development - Inkyung Kim (Korea Development Institute (KDI), 2021)
As the COVID-19 pandemic highlighted the need to further strengthen education and childcare, this study looks at the correlation between the participation of elementary school students in after-school programs and their child development and then offers recommendations for developmental outcomes among elementary school children through after-school activities. After-school programs are educational and caring activities that schools offer for a certain period apart from the regular school curriculum, tailored to the needs of students and parents. Students choose a course from a list of diverse program options, encompassing school subjects and special talent and aptitude programs. The analysis finds no consistent correlation between participation in after-school activities and the development of elementary school students. As for the after-school program, less than one hour of participation led to better health status assessments, and for two to three hours, there were improvements in academic vigor, grit, and body mass index (BMI) but decreased aggressiveness, depression, and peer relationship. In contrast, physical symptoms worsened when participating for two or more hours. Such results may be attributed to the differences between the programs, such as varying content composition depending on operating hours, teaching methods, and instructor characteristics. For after-school programs to shore up student competencies, they should share student guidance information with regular classes, form a close link with the regular curriculum, and provide sufficient care backed by positive interactions. Provided that student information such as interests, experiences, developmental characteristics, learning history, etc., is exchanged between elementary school courses and after-school programs, the extracurricular activities may provide in-depth stimulation for learning based on the data. Affectionate and nurturing care is a prerequisite to bringing out students' potential. It is necessary to expand the instructor pool competent in achieving the well-rounded development of children, widen the scope of after-school program providers to local communities, and have local governments take a managing role over the programs for efficient and effective management. In addition to providing compulsory training courses for prospective after-school instructors, the instructor selection process should adopt multi-faceted personality interviews to find out candidates' responses about a given classroom situation for a comprehensive assessment. Local governments should play a managing role in planning, promoting, and overseeing after-school activities in the region, including after-school programs at schools. Meanwhile, schools should actively engage and cooperate within this framework by informing after-school program registration details and providing a venue.
Keywords: 330